“Tahu Salah Tapi Mahu”: cabaran remaja perempuan berhenti menonton pornografi - Norulhuda Sarnon@Kusenin,; Nur Hamizah Mohd Sharif,; Daniella Maryam Mohd Mokhtar,; Siti Marziah Zakaria,; Ezarina Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study aims to explore how much female adolescents are willing to stop watching pornography and the challenges they face in abandoning their behavior. This qualitative study uses a phenomenological approach to understand the personal experiences of the adolescents involved. Given that the issue of pornography is considered ‘taboo’, only five adolescents who have engaged in pornography have voluntarily agreed to be interviewed in depth by adhering to established criteria and data saturation. They consist of late teens between the ages of 19 and 21 and are students from a public college. Data was collected via in-depth interviews based on semi-structured questions to achieve the research objectives. The questions are based on the Transteoretic Model with a focus on the readiness and challenges of abandoning pornographic behavior. The results of this study found that all respondents were less serious about change despite having the knowledge and awareness that watching pornography had a negative impact. The study also identified five challenges faced by respondents in abandoning pornographic behavior that were (i) incapable of controlling their appetite, (ii) internet attraction, (iii) filling their loneliness, (iv) their habit and (v) the way of thinking. The findings of this study are discussed by linking issues of internet addiction and the change model. Besides that, suggestions for referral to professionals in the help profession are also discussed.